The molecular function of kallikrein-related peptidase 14 demonstrates a key modulatory role in advanced prostate cancer - Kryza,T; Bock,N; Lovell,S; Rockstroh,A; Lehman,ML; Lesner,A; Panchadsaram,J; Silva,LM; Srinivasan,S; Snell,CE; Williams,ED; Fazli,L; et al. (Molecular Oncology, 2020)
Kallikrein-related peptidase 14 (KLK14) is one of several secreted KLK serine proteases involved in prostate cancer (PCa) pathogenesis. While relatively understudied, recent reports have identified KLK14 as overexpressed during PCa development. However, the modulation of KLK14 expression during PCa progression and the molecular and biological functions of this protease in the prostate tumour microenvironment remain unknown. To determine the modulation of KLK14 expression during PCa progression, we analysed the expression levels of KLK14 in patient samples using publicly available databases and immunohistochemistry. In order to delineate the molecular mechanisms involving KLK14 in PCa progression, we integrated proteomic, transcriptomic and in vitro assays with the goal to identify substrates, related-signalling pathways and functional roles of this protease. We showed that KLK14 expression is elevated in advanced PCa, and particularly in metastasis. Additionally, KLK14 levels were found to be decreased in PCa tissues from patients responsive to neo-adjuvant therapy compared to untreated patients. Furthermore, we also identified that KLK14 expression re-occurred in patients who developed castrate-resistant PCa. The combination of proteomic and transcriptomic analysis as well as functional assays revealed several new KLK14-substrates (agrin, desmoglein 2, vitronectin, laminins) and KLK14-regulated genes (Interleukin 32, midkine, Sox9), particularly an involvement of the MAPK1 and IL1RN pathways, and an involvement of KLK14 in the regulation of cellular migration, supporting its involvement in aggressive features of PCa progression. In conclusion, our work showed that KLK14 expression is associated with the development of aggressive PCa suggesting that targeting this protease could offer a novel route to limit the progression of prostate tumours. Additional work is necessary to determine the benefits and implications of targeting/co-targeting KLK14 in PCa as well as to